La presenza di Gramsci nella prima e nella seconda serie di “Critica Marxista” - Liguori, Guido (International Gramsci Journal, 2023)
This is the Abstract of the description in Italian by Guido Liguori of the presence of articles regarding Gramsci in the Italian review “Critica marxista”.